On Formalizing and Normalizing Role-Based Access Control Systems - Power, D; Slaymaker, M; Simpson, A (2009)
Role-based access control (RBAC) has emerged as the dominant access control paradigm for service-oriented systems, with this dominance being reflected by the popularity of RBAC both with the research community and with information technology vendors. RBAC's dominance was solidified in 2004 when an American National Standards Institute standard for RBAC was approved. In this paper, we consider some of the drawbacks of this standard and show how the formal description technique, Z, has been used to underpin a model of RBAC. The model builds on the work of Li et al. and adopts a modular approach. In particular, we consider the relationships between different types of inheritance within our model. We show our model can be used to define a notion of equivalence between different RBAC systems. Finally, we show how - via our model - a particular RBAC system can be normalized to produce a simpler - but semantically equivalent - representation. We illustrate this process via two examples. © The Author 2008. Published by Oxford University Press on behalf of The British Computer Society. All rights reserved.